2015
DOI: 10.1002/sec.1214
|View full text |Cite
|
Sign up to set email alerts
|

A new authentication protocol for healthcare applications using wireless medical sensor networks with user anonymity

Abstract: With the development and maturation of the wireless communication technologies, the wireless sensor networks have been widely applied in different environments to acquire specific information. The wireless medical sensor networks (WMSNs), as a professional application of the wireless sensor networks in medicine, have attracted more and more attention because of its potential in improving the quality of healthcare services. Through the WMSNs, the parameters of patients' vital signs can be gathered from the sens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
168
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 138 publications
(168 citation statements)
references
References 36 publications
(68 reference statements)
0
168
0
Order By: Relevance
“…Li et al [23] showed that He et al's scheme was under the de-synchronization attack. This attack occurs if there is some inconsistency in a legal users normal authentication process.…”
Section: Discussion Of the De-synchronization Attackmentioning
confidence: 99%
See 2 more Smart Citations
“…Li et al [23] showed that He et al's scheme was under the de-synchronization attack. This attack occurs if there is some inconsistency in a legal users normal authentication process.…”
Section: Discussion Of the De-synchronization Attackmentioning
confidence: 99%
“…This will lead to the failure of subsequent authentication. [23] criticized the password change phase, which is under the de-synchronization attack. We only use their conclusion and omit the phase here.…”
Section: Discussion Of the De-synchronization Attackmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, it is widely accepted that an adversary has the full control of the channel; that is, A can intercept, delete, modify, resend, and reroute the messages in an open channel [33][34][35]. Furthermore, A may also learn users' passwords via a malicious terminal or extract the parameters from the smart card by side-channel attack, but cannot achieve both [2,27,36].…”
Section: Adversary Modelmentioning
confidence: 99%
“…However, we find that Shim's proposed improved protocol is unworkable because the signature verification does not hold true. Among various secure protocols in WSNs [3][4][5][6][7][8][9][11][12][13][14][15][16][17][18][19][20][21][22][23][24], most of the published reprogramming protocols [3, 6, 12-14, 16, 18, 20-23] are based on the centralized approach, which assumes the existence of a base station, and only the base station has the authority to reprogram sensor nodes. The centralized approach is not reliable in reality because of inefficiency, weak scalability, and vulnerability to potential attacks along the communication path [24].…”
Section: Introductionmentioning
confidence: 99%